Study satisfaction among university students during the COVID-19 pandemic: Longitudinal development and personal-contextual predictors - Gadosey, Christopher K.; Grunschel, Carola; Kegel, Lena S.; Schnettler, Theresa; Turhan, Derya; Scheunemann, Anne; Bäulke, Lisa; Thomas, Laura; Buhlmann, Ulrike; Dresel, Markus; Fries, Stefan; Leutner, Detlev; et al. (Frontiers in Psychology, 2022)
The COVID-19 pandemic challenges the well-being and academic success of many students. Yet, little is known about students’ study satisfaction during the COVID-19 pandemic, a multilayered construct which accounts for students’ subjective cognitive well-being and academic success. Besides, previous studies on study satisfaction are mostly cross-sectional and hardly consider the distinct subdimensions of this construct. Therefore, our main goal in the current research was to shed light on the understudied development of the subdimensions of study satisfaction (i.e., satisfaction with study content, conditions of studying, and coping with study-related stress) in two semesters amid the COVID-19 pandemic. Additionally, we examined how particular personal (i.e., gender, age, GPA, intrinsic motivation, motivational cost, and academic procrastination) and contextual (i.e., loneliness) factors related to these subdimensions. We conducted two panel studies with convenience and purposeful samples of university students in Germany (Nstudy1 = 837; Nstudy2 = 719). Participants responded online to questions on each of the subdimensions of study satisfaction at the beginning, middle and end of each semester but responded to measures of personal and contextual factors only at the beginning of each semester. In both studies, manifest growth curve models indicated a decrease in all subdimensions of study satisfaction as the semester progressed. Generally, gender (male) and intrinsic motivation were positive predictors but age (younger students), motivational cost, and loneliness were negative predictors of different subdimensions of study satisfaction – particularly satisfaction with study content. Overall, motivational costs and loneliness were the most consistent predictors of all subdimensions of study satisfaction across both studies. Our findings provide support for the understanding that study satisfaction could diminish in the face of challenging situations such as in this pandemic. The present study also highlights certain personal and contextual factors that relate to study satisfaction and calls for intensive research into the multidimensional construct of study satisfaction.